Answer:
Y = (-3) *X - 10
solution for Y =0 ---> X = -10/3
Explanation:
Two points:
(Y0 ; X0) = (-4 ; 2)
(Y1 ; X1) = (-2 ; -4)
There is only one line which pass for both of them, his general expresion is:
y = a*x + b --- (1)
Calculating "a": is the pending of the line.
![a = (Y1 - Y0)/(X1 - X0) = ((-4) - (2))/(-2 - (-4)) =(-6)/(2) = -3](https://img.qammunity.org/2021/formulas/mathematics/high-school/hdluxirc56ploa0y81ekwxv06dcswx3kgy.png)
Calculating "b":
Since every point who belongs to the line satisfied the (1) expresion, we can use it for the point (Y1 ; X1) :
![Y0 = (-3)*X0 + b ---> 2 = (-3)*(-4) + b ---> b = -10](https://img.qammunity.org/2021/formulas/mathematics/high-school/qd9a1k685y2l4c0my17etddmivnye8aohj.png)
Final expresion
Replacing in (1):
![Y = (-3) *X - 10](https://img.qammunity.org/2021/formulas/mathematics/high-school/y6vyon8jqysstn0aw1bwf1piom9nlp30zy.png)
Solutions: